RETAIL LOAN PERFORMANCE IN INDIA: AN EMPIRICAL STUDY IN PUBLIC AND PRIVATE SECTOR BANKS - Murugaboopathy L; Goel , Rinku S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Using an empirical methodology, this study investigates the performance of retail loans in Indian public and private sector banks, with a focus on house and education loans. It seeks to assess important performance metrics including borrower satisfaction, default rates, repayment trends, and loan disbursement trends. 120 respondents, evenly divided across the two banking sectors, provided primary data using structured questionnaires as part of a descriptive study methodology. According to the data, public sector banks are more active in offering education loans while having higher default rates, whereas private sector banks perform better in terms of efficiency, recovery rates, and customer satisfaction, particularly in the housing loan area. Suggestions for enhancing risk management and service provision in retail banking are included in the study's conclusion.